Histochemical and ultrastructural evidence of lipid secretion by the silk gland of the sugarcane borer Diatraea saccharalis (Fabricius) (Lepidoptera: Crambidae) - Victoriano, Eliane [UNESP]; Pinheiro, Daniela O. [UNESP]; Gregório, Elisa A. [UNESP] (Springer Nature, 2007)
The silk gland in Lepidoptera larvae is responsible for the silk production used for shelter or cocoon construction. The secretion of fibroin and sericin by the different silk gland regions are well established. There are few attempts to detect lipid components in the insect silk secretion, although the presence of such element may contribute to the resistance of the shelter to wet environment. This study characterizes the glandular region and detects the presence of lipid components in the secretion of the silk gland of Diatraea saccharalis (Fabricius). The silk gland was submitted to histochemical procedure for lipid detection or conventionally prepared for ultrastructural analyses. Lipid droplets were histochemically detected in both the apical cytoplasm of cell of the anterior region and in the lumen among the microvilli. Ultrastructural analyses of the anterior region showed lipid material, visualized as myelin-like structures within the vesicular Golgi complex and in the apical secretory globules, mixed up with the sericin; similar material was observed into the lumen, adjacent to the microvilli. Lipids were not detected in the cells neither in the lumen of the posterior region. Our results suggest that the silk produced by D. saccharalis has a minor lipid content that is secreted by the anterior region together with the sericin.
Evidências histoquímicas e ultra-estruturais de secreção sipídica pela glândula da seda da broca da cana-de-açúcar, Diatraea saccharalis (Fabricius) (Lepidoptera: Crambidae)
Keywords: Insect; Larva; Secretory cell; lipid; animal; exocrine gland; histology; larva; Lepidoptera; physiology; secretion; sugarcane; ultrastructure; Animals; Exocrine Glands; Lipids; Saccharum; Crambidae; Diatraea saccharalis; Hexapoda